Being in two places at once: renegotiating traumatic experience through the surplus reality of psychodrama. Issue 3 (3rd July 2019) - Giacomucci, Scott; Stone, Amy
ABSTRACT: This article continues the dialogue started by Skolnik 2018 about the synergistic union of social work and psychodrama group approaches. The theoretical and clinical alignment of psychodrama and sociometry with social work with groups will be described. A practice illustration from Mirmont Treatment Center will be presented and discussed to explore some of the dynamics of psychodrama and, in particular, the therapeutic value of surplus reality. Surplus reality is a creative tool used to provide a therapeutic corrective emotional experience. Integrating insights from neuroscience, this article advocates for psychodrama as a valuable modality for clinical social workers engaged in group work.